2018
DOI: 10.1039/c7qi00742f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of plasmon induced Ag@Ag3VO4/ZnCr LDH ternary heterostructures towards visible light responsive O2 evolution and phenol oxidation reactions

Abstract: The SPR effect of monodisperse Ag nanoparticles in Ag@Ag3VO4/ZnCr LDH heterostructures exhibits high photocatalytic activity towards evolution of O2 and oxidation of phenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 75 publications
1
52
0
Order By: Relevance
“…The resulting compound was characterized by a variety of characterization means, and its catalytic performance was investigated for the so-called "Mukaiyama" epoxidation of olefins, in which molecular oxygen was used as the oxidant and isobutyraldehyde was used as the co-reagent. Previous literature studies suggested that a few Ag-complexes are moderately active homogeneous catalysts for these attractive O 2 -mediated hydrocarbon/olefin oxidation processes [19][20][21][22][23][24]. Our present work shows that the hybrid polycatenane compound shows much higher catalytic activity than the corresponded POM or Ag-trz complexes.…”
Section: Introductionsupporting
confidence: 48%
“…The resulting compound was characterized by a variety of characterization means, and its catalytic performance was investigated for the so-called "Mukaiyama" epoxidation of olefins, in which molecular oxygen was used as the oxidant and isobutyraldehyde was used as the co-reagent. Previous literature studies suggested that a few Ag-complexes are moderately active homogeneous catalysts for these attractive O 2 -mediated hydrocarbon/olefin oxidation processes [19][20][21][22][23][24]. Our present work shows that the hybrid polycatenane compound shows much higher catalytic activity than the corresponded POM or Ag-trz complexes.…”
Section: Introductionsupporting
confidence: 48%
“…Such changes in the binding energies are generated because the electron density of NH 2 -MIL-125(Ti) decreases and that of ZnCr-LDH NSs increases. These findings clearly indicate that there exists an effective electronic coupling between the two components because of the hybridization, leading to not only the harvest of more incident photons to produce more photo-generated electrons and holes but also the suppression of the recombination of photo-generated electron and hole pairs due to an effective electron transfer between NH 2 -MIL-125(Ti) and ZnCr-LDH NSs 38,39 .
Figure 7XPS spectra of (bottom in a , b , e ) pristine NH 2 -MIL-125(Ti), (bottom in c , d ) pristine ZnCr-LDH and (top in a – e ) the ML200 hybrid composite: ( a ) the full-spectrum survey, ( b ) Ti 2p, ( c ) Zn 2p, ( d ) Cr 2p and ( e ) O 1 s.
…”
Section: Introductionmentioning
confidence: 89%
“…34 Recently, our group has reported Ag@Ag 3 VO 4 /ZnCr LDH heterostructure systems toward photocatalytic water oxidation and phenol degradation reaction. 35 However, no reports on the study of the heterostructure Ag@Ag 3 PO 4 /CNLDH nanocomposite as the photocatalyst and how the SPR electrons of Ag NPs together with Ag 3 PO 4 can participate in effective charge separation and protect the structural stability of exfoliated NiFe LDH nanosheets in this system have still been scarcely developed up to now.…”
Section: Introductionmentioning
confidence: 99%